2017
DOI: 10.1037/emo0000268
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical systems modeling of early childhood self-regulation.

Abstract: Self-regulation can be conceptualized in terms of dynamic tension between highly probable reactions (prepotent responses) and use of strategies that can modulate those reactions (executive processes). This study investigated the value of a dynamical systems approach to the study of early childhood self-regulation. Specifically, ordinary differential equations (ODEs) were used to model the interactive influences of 115 36-month-olds’ executive processes (strategy use) and prepotent responses to waiting to open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 70 publications
(138 reference statements)
2
57
0
1
Order By: Relevance
“…Surprisingly, most longitudinal studies that assess self‐regulation study it as a predictor, moderator, or outcome, and do not focus on how self‐regulation changes with age. Evidence supports Kopp's () proposition that young children initiate strategic attempts without adult direction, but evidence also indicates that their strategies are effective only momentarily (Buss & Goldsmith, ; Cole et al., ). Being able to tolerate challenges, in more than just a momentary way, is necessary to be ready for school (Blair & Raver, ).…”
Section: Self‐regulation As a Dynamic Processmentioning
confidence: 59%
See 2 more Smart Citations
“…Surprisingly, most longitudinal studies that assess self‐regulation study it as a predictor, moderator, or outcome, and do not focus on how self‐regulation changes with age. Evidence supports Kopp's () proposition that young children initiate strategic attempts without adult direction, but evidence also indicates that their strategies are effective only momentarily (Buss & Goldsmith, ; Cole et al., ). Being able to tolerate challenges, in more than just a momentary way, is necessary to be ready for school (Blair & Raver, ).…”
Section: Self‐regulation As a Dynamic Processmentioning
confidence: 59%
“…Second, a dynamic approach can address when and how effective self‐regulation manifests, and the many ways that behavior reveals competence and difficulty. For example, among 36‐month‐olds in one study, EP had momentary influence but not enduring damping of PR (Cole et al., ), and variations in their interplay were associated with particular between‐person differences. The presence of externalizing behavior problems predicted PR damping EP rather than the reverse, and higher temperamental negative affectivity predicted EP amplifying rather than diminishing PR.…”
Section: Self‐regulation As a Dynamic Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, few studies have examined the influence of PR on EP (e.g., Ekas et al., ), and to our knowledge, no study (with the exception of Cole et al., ) has examined the effects of PR on EP while taking into account the effects of EP on PR. The current findings on the influence of PR on EP highlight the importance of using models that capture the bidirectional dynamics of the self‐regulatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach investigates bidirectional influences of PR and EP, allowing us to ask, for example, whether there are age-related changes in the tendency of PR to interfere with EP effectiveness. Recently, it was shown that for some 3-year-olds, if the level of PR is too high, it can overwhelm EP, regulatory interference (Cole, Bendezú, Ram, & Chow, 2017). In the context of fear, a toddler may freeze and use fewer strategies (Buss & Goldsmith, 1998;Buss, Davidson, Kalin, & Goldsmith, 2004).…”
Section: Limitations In Operationalizing Self-regulationmentioning
confidence: 99%